2006
DOI: 10.1177/0040517506060140
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of Cotton Cellulose in the Presence of Alpha-aminoacids Part III: Pore Structures

Abstract: The changes of the absorption bands of the infrared spectra for the cured dimethyloldihydroxyethyleneurea(DMDHEU)-aspartic acid in our previous study [1] revealed that the -OH group of DMDHEU could react with the amino and carboxylic acid groups of aspartic acid. In that study, we also found that the values of wet crease recovery angle (WCRA) and tensile strength retention (TSR) of the fabrics treated with DMDHEU-alpha-amino acids were higher, and dry recovery angles were lower than those expected from DMDHEU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…IR spectra of the samples were obtained using a KBr disk technique [8]. Samples were prepared to give a dry weight of 1.8 mg after storage in 1-dram vials over P 2 O 5 for three days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra of the samples were obtained using a KBr disk technique [8]. Samples were prepared to give a dry weight of 1.8 mg after storage in 1-dram vials over P 2 O 5 for three days.…”
Section: Methodsmentioning
confidence: 99%
“…studies [3,7] pointed out that the carboxylic acid of tartaric acid could interact with aluminum ion to release hydrogen ions to improve the catalytic effect, the crease recovery angles and the reaction rate constants. Our previous studies [8,9] showed that the physical properties of the treated fabrics with DMDHEU/alpha-amino acids were changed with the kinds of alpha-amino acids used.…”
mentioning
confidence: 99%